Palliative care nursing caring for suffering patients - Perrin, Kathleen Ouimet; Kazanowski, Mary K.; Potter, Mertie L.; Sheehan, Caryn A. (Jones & Bartlett Learning, 2023)
"Palliative Care Nursing: Caring for Suffering Patients explores the concept of suffering as it relates to nursing practice. This text helps practicing nurses and students define and recognize various aspects of suffering across the lifespan and within various patient populations while providing guidance in alleviating suffering. In addition, it examines spiritual and ethical perspectives on suffering and discusses how witnessing suffering impacts nurses' ability to assume the professional role. Further, the authors discuss ways nurses as witnesses to suffering can optimize their own coping skills and facilitate personal growth. Rich in case studies, pictures, and reflections on nursing practice and life experiences, Palliative Care Nursing: Caring for Suffering Patients delves into key topics such as how to identify when a patient is suffering, whether they are coping, sources of coping facades, what to do to ease suffering, and how to convey the extent of suffering to members of the health care team.Palliative Care Nursing: Caring for Suffering Patients helps practicing nurses and students define and recognize various aspects of suffering across the lifespan and within various patient populations while providing guidance in alleviating suffering"--